PARENTAL MEDIATION PADA ANAK SAAT MENONTON TELEVISI DENGAN RATING GUIDE BIMBINGAN ORANG TUA (R-BO) - Kaloka, Rintulebda Anggung (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
ABSTRACTTelevision has few negative side especially for children. Television gives rated PG (Parental Guidance) in certain programs. To minimize the negative effects of television for children hence the need for parental mediation. seeing the impact of television programs and the lack of assistance parents when children watch television feared could affect a child's development.Keywords: Parental Mediation, Rating Guide, Television